Paeonia anomala (Paeoniaceae) component composition and antioxidant, antiradical and cytotoxic activity - Sarkytbayeva, A.K.; Kubentayev, S.A.; Kurmanbayeva, M.S.; Aidarkhanova, G.S.; Iskakova, Zh.B.; Zhumagul, M.Zh.; Kusmangazinov, A.B. (Fundamental and Experimental Biology, 2023)
Paeonia anomala L. is a valuable medicinal plant in the world. The aim of this study was the study of composition of the plant P. anomalaand its antioxidant, antiradical and cytotoxic activities. The underground part of P.anomalawas extracted with ethanol and the composition was determined using gas chromatography with mass spectrometric detection (Agilent 7890A/5975C). Methyl salicylate (32.07%), sucrose (11.23%), benzoic acid (9.12%), cyclopropyl carbine (7.7 %), 2,5-dimethyl-4-hydroxy-3(2H)-furanone (4.77%), ben-zoic acid, 2,4-dihydroxy-3,5,6-trimethyl-, methyl ester (4.48%), are the main components. The ethyl acetate extract of the underground part (root) of P. anomalaat concentrations of 0.25 and 0.5 mg/ml has a low content, and at concentrations of 0.75 and 1 mg/ml, an average antioxidant activity compared to the antioxidant activity ofascorbic and gallic acids. The ethanol extract of the underground part of P. anomalaat concentrations of 0.25 and 0.5 mg/ml has an average, and at concentrations of 0.75 and 1 mg/ml the highest antioxidant activity compared to the antioxidant activity comparators. Also, the ethanol extract of the underground part P.anomalahas the highest antiradical activity in all concentrations compared to the antiradical activity of gallic acid. Ethanol and ethyl acetate extracts of the underground part of P. anomalain all concentrations do not show cytotoxicity.